Silicon oxidation by NAPPES: From dangling bonds to oxygen islands to 2D SiOx layer to the onset of bulk SiO2 formation - Ghosalya, Manoj Kumar; Jain, Ruchi; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2018)
Valence band and core level photoelectron spectral measurements at near-ambient pressures (NAP; up to 0.5 mbar) were made in the presence of molecular oxygen to explore the various oxidation stages of silicon surfaces. Dangling bonds feature observed on clean Si-surfaces in the valence band at ultrahigh vacuum decreases dramatically due to oxygen adsorption between ambient temperature and up to 400 K at 0.1 mbar of O-2 pressure. The adsorption of oxygen on dangling bonds appears to be localized as islands; this reflects in the surface heterogeneous character and also responsible for the broadening in the oxygen gas phase vibrational features. This is further supported by an increase in the work function and can be correlated to the presence of Hofer (molecular) precursor. When the temperature was increased to 500 K, molecular precursor species dissociates to form Si-=-0 species. This is fully supported by the change in the Si work function as well as from the observation of oxidized Si species from Si 2p core level spectra. At >= 600 K, the Si-=-0 species dissociates to form a uniform 2D oxide layer on the silicon surface, which is characterized by the reappearance of sharp vibration features for gas-phase O-2 molecules. This layer is also quite stable up to 800 K and without any further oxidation in the bulk. On increasing the temperature to 850 K at 0.2 mbar oxygen pressure, bulk Si oxidation begins and the work function increases drastically by 1 eV. An angle-dependent Si 2p spectra recorded map out the presence of elemental Si to Si4+ from bulk to the surface, respectively. A simple model is proposed to show the various stage of silicon oxidation. A continuous change in the work function and electronic states observed due to gas-lattice (O-2-Si) interaction indicates the implications for surface-dependent phenomena, such as heterogeneous catalysis, electrochemistry, 2D layered materials.